Traditional Chinese herbal formula relieves snoring by modulating activities of upper airway related nerves in aged rats - Chung KT; Hsu CH; Lin CL; Wang SE; Wu CH (Dove Medical Press, 2018)
Kou-Toung Chung,* Chih-Hsiang Hsu,* Ching-Lung Lin, Sheue-Er Wang, Chung-Hsin WuDepartment of Life Science, National Taiwan Normal University, Taipei, Taiwan*These authors contributed equally to this workAim: The present study investigated whether intraperitoneal treatment with the herbal formula B210 ([B210]; a herbal composition of Gastrodia elata and Cinnamomum cassia) can reduce snoring in aged rats. Also, we studied possible neural mechanisms involved in B210 treatment and subsequent reduced snoring in rats.Methods and result: We compared pressure and frequency of snoring, activities of phrenic nerve (PNA), activities of recurrent laryngeal nerve (RLNA) and activities of hypoglossal nerve (HNA), inspiratory time (TI) and expiratory time (TE) of PNA, and pre-inspiratory time (Pre-TI) of HNA in aged rats between sham and B210 treatment groups (30 mg/mL dissolved in DMSO). We found that aged rats that received B210 treatment had significantly reduced pressure and frequency of snoring than rats who received sham treatment. Also, we observed that aged rats that received B210 treatment had significantly increased PNA, RLNA, and HNA, extended TI and TE of PNA, and prolonged Pre-TI of HNA compared to rats that received sham treatment. In other words, B210 treatment may relieve snoring through modulating activities and breathing time of upper airway related nerves in aged rats.Conclusion: We suggested that the B210 might be a potential herbal formula for snoring remission.Keywords: Chinese herbal medicine, snoring remission, upper airway, phrenic nerve, recurrent laryngeal nerve, hypoglossal nerve